موقف مالك بن نبي من قضايا عصره الاستشراق و الغزو الفكري -أنموذجا - شيخة مبروك, خديجة; رويسي, إيمان (University of Eloued-جامعة الوادي, 2022)
في دراستنا التي تحمل عنوان "" موقف مالك بن نبي من قضايا عصره الاستشراق والغزو الفكري ــ أنموذجا ــ"" كان الهدف منها إبراز وجهة نظر مالك بن نبي من الأفكار الوافدة مثل الاستشراق والغزو الفكري، إذ هو تحدي معاصرة المفكر ّمالك بن نبي في بلدان عدة لأفكار وافدة على العالم العربي والإسلامي، والتحدي الأصعب هو تكوينه بلسان فرنسي وتأثره بألفكار الغربيةفيالنهضة والتطور، كما كمان له تحدي آخر هو مرحلة الاستعمار واضطراب الأوضاع ما بعد الاستقلال، وما واجهه من محاصرات استعمارية وطر د من بلده مما أدى به للفرار لى لبنان ومصر، فلم يكن لسانه الفرنسي أو تأثره بالغرب حاجزا لتوضيح ما أتى به الاستشراق والغزو الفكري والإقلاع بالحضارة الاسلامية، ووضع أسس ومرتكزات لبناء الحضارة الإسلامية المنشودة."In our study entitled ""Malik Bin Nabi from the issues of his time orientalism and intellectual invasion model"", the aim was to highlight malik bin Nab's destination from the ideas of the coming, such as orientalism and intellectual invasion, as he is a contemporary thinker Malik Bin Nabi in several countries for ideas coming to the Arab and Islamic world, and the most difficult talk is to form it with a French tongue and influence western ideas in renaissance and development, as it had another challenge is colonialism and post-independence unrest, and what was He was confronted by colonial sieges and expelled from his country, which led him to flee to Lebanon and Egypt, but his French tongue or influenced by the West did not be a barrier to clarify what orientalism, intellectual invasion and take-off of Islamic civilization brought, and to lay the foundations and foundations for the desired Islamic civilization, as Malik ibn Nabi sees it."
مذكرة ماستر
Keywords: مالك بن نبي.الاستشراق.الغزو الفكري; Malik Bin Nabi. Orientalism. Intellectual Invasion